STUDY OF THE PROCESS OF RECOVERY OF IRON OXIDES BY HIGH-TEMPERATURE HYDROGEN-CONTAINING GAS IN AN ELECTROTHERMAL PSEUDO-FLUIDIZED LAYER - Simeiko, Kostyantyn; Zagrebelnyi, Oleksiy; Ryabchuk, Valery; Trofimov, Ihor; Shulga, Oleg (Problems of Friction and Wear, 2023)
Hydrogen metallurgy involves the replacement of a carbon reducing agent with a hydrogen one. One of the promising opportunities for the use of hydrogen in metallurgy is the recovery of iron ore pellets that consist of iron oxides. However, there is a problem of heating the hydrogen-containing gas to the recovery temperature. One of the possible solutions to this problem is the use of an electrothermal fluidized bed. The purpose of the article was to determine the principle possibility of recovery of iron oxides in the form of iron ore pellets by high-temperature hydrogen-containing gas in an electrothermal fluidized bed. The authors considered the generation of hydrogen by pyrolysis of natural gas. Conducted thermodynamic calculations of the process of reduction of iron oxides with the obtained hydrogen indicate the optimal temperature range of the process: 900 ... 1500 K. To study this process, a laboratory installation with an electrothermal fluidized bed with a combined heating method was created. This installation is divided into two reaction zones. In the first, natural gas is decomposed into hydrogen and pyrocarbon. Carbon dioxide, which is a valuable material, remains in the first reaction zone. The formed hydrogen with a high temperature enters the second reaction zone where it restores the iron ore pellets. During the process of recovery of iron pellets with high-temperature hydrogen-containing gas, no flame accompanying the process of hydrogen formation by pyrolysis of hydrocarbons was detected. The release of water vapor at the reactor outlet was observed. This means that the hydrogen produced reacted with the iron pellets and reduced them to pure iron. The surface microstructure of the original iron pellet is darker and matte, while the surface microstructure of the processed iron pellet has a lighter color and a shiny surface, which is characteristic of pure metals. This additionally indicates the fundamental possibility of restoring iron pellets to pure iron with high-temperature hydrogen produced by pyrolysis of natural gas in an electrothermal fluidized bed. Research results can be applied in the energy sector, the transport sector, in particular, in the operation of space vehicles. The results of the article can be applied in practice by energy engineers, expert chemists, as well as scientists involved in the development of the latest technologies for obtaining hydrogen.